Gas Chromatographic/Mass Spectrometric Analysis of Volatile Metabolites in Bovine Vaginal Fluid and Assessment of Their Bioactivity. (25th October 2011) - Sankar, R.; Archunan, G.
Abstract : The chemical profiles of vaginal fluid collected from cows in oestrus and nonoestrus were analysed by gas chromatography-mass spectrometry (GC-MS) to establish any qualitative differences that might have potential value in bovine biocommunication. Eight different organic compounds were detected using the two chromatograms. The chemical profiles of oestrus vaginal fluid were distinguished significantly by the presence of three specific substances, namely, trimethylamine, acetic acid, and propionic acid that were not present in nonoestrus phase. The oestrus specific synthetic compounds were rubbed onto the genital region of nonoestrus animals (dummy cows), and the bulls were allowed to sniff the genital region and observed sexual behaviours. The statistical significance was higher (P < 0.001 ) in bulls exhibiting repeated flehmen and mounting behaviours towards the mixture of acetic acid, propionic acid, and trimethylamine as compared to test these compounds separately. It was concluded that the volatile substances present in the bovine vaginal fluid during oestrus may act as chemical communicators.